Optimizing MOOCs in Islamic Education Institutions: Digital Learning Tools in Era 5.0 - Fadhilah, Lailaturrohmah; Putri, Zifa Ayu (Proceeding International Conference on Religion, Science and Education, 2025)
The industrial era 5.0 is a phase of industrial development that focuses on collaboration between humans and technology. This era not only impacts the industrial sector, but also impacts the education sector so that various online learning platforms emerge, one of which is MOOCs (Massive Open Online Course). MOOCs provides various materials needed by students that can be accessed online, anywhere and anytime. Islamic educational institutions can use MOOCs as a means of learning in the industrial era 5.0 which accelerates knowledge and technology. This certainly requires every Islamic educational institution to keep abreast of existing technological developments, and minimize the lag of rapid changes in the times. This research discusses how MOOCs is used as a means of digital learning to improve the quality, accessibility and competitiveness of Islamic educational institutions in the world of education in the 5.0 era. This research uses library research methods by using relevant journals and books as research data sources. The results of this study indicate that MOOCs as a digital learning tool has a major impact on the learning process, one of which is expanding access to learning, being flexible and affordable, and making learning sustainable. However, MOOCs has its own challenges in the learning process such as lack of interaction between teachers and students, technical constraints and low learning completion rate. Therefore, it is important for Islamic education institutions to integrate interactive features such as discussion and Q&A forums, ensure adequate technical support and develop more structured learning modules in order to increase motivation and learning completion rates.